Thanks a lot, Universe - Lucas, Chad (Amulet Books, 2021)
"Brian has always been anxious, whether at home or in class or on the basketball court. His dad tries to get him to stand up for himself, and his mom helps as much as she can, but after he and his brother are placed into foster care, Brian starts having panic attacks. And he doesn't know if things will ever be 'normal' again ... Ezra's always been popular. He's friends with most of the kids on his basketball team--even Brian, who usually keeps to himself. But now, some of his friends have been acting differently, and Brian seems to be pulling away. Ezra wants to help, but he worries if he's too nice to Brian, his friends will realize that he has a crush on him ... But when Brian and his brother run away, Ezra has no choice but to take the leap and reach out. Both boys have to decide if they're willing to risk sharing parts of themselves they'd rather hide. but if they can be brave, the might just find the best in themselves--and each other."--